STUDI PERANCANGAN KAPAL PINTAR UNTUK MENUNJANG KEGIATAN PENDIDIKAN DI KAWASAN KEPULAUAN SERIBU - Pardamean, Overt Elois; Budi Santoso, Ari Wibawa; Mulyatno, Imam Pujo (Jurnal Teknik Perkapalan, 2013)
The lack of educational facilities in rural coastal and outermost small islands is a major consideration in the design of Kapal Pintar. The design of this ship serves as a means of education that provides books that are educating for early childhood and has four central facilities, the Book Centers, Computer Centers, Center for Educational Games, Tools and Audio Visual Center and stage. So the main function of the ship which is used as a means of education is required designed and made as comfortable as possible and has complete facilities. This research is conducted by doing some steps of design, that are main dimention calculations, making the lines plan, general arrangement, hydrostatic, stability analysis of the vessel also motion of the ship. And selection ship equipments, main engine according to the calculation of engine power accordance to the resistance experienced by the ship. Results of design this ship got main dimension LOA :16,00 m, Lwl: 15,76 m, B: 5,2 m, T: 0,7 m, H: 1,8 m. From hydrostatic results, catamaran multifunction of Semarang West Flood Way has a displacement 12,825 ton, Cb: 0.404, LCB : 7,437 m.  On review of stability, the results indicate stability of the vessel has a stable, point M is above G point in all conditions. Ship motion, have proved a good move, it does not happen deck wettnes Meanwhile, the ship's passenger capacity is 20 persons with 4 crew. The ship was to use two propulsion diesel engine outboard motors with power generated by 30 HP.